Salicylic acid-induced abiotic stress tolerance and underlying mechanisms in plants - Khan, M. Iqbal R.; Fatma, Mehar; Per, Tasir S.; Anjum, Naser A.; Khan, Nafees A. (Frontiers in Plant Science, 2015)
Abiotic stresses (such as metals/metalloids, salinity, ozone, UV-B radiation, extreme temperatures and drought) are among the most challenging threats to agricultural system and economic yield of crop plants. These stresses (in isolation and/or combination) induce numerous adverse effects in plants, impair biochemical/physiological and molecular processes, and eventually cause severe reductions in plant growth, development and overall productivity. Phytohormones have been recognized as a strong tool for sustainably alleviating adverse effects of abiotic stresses in crop plants. The significance of salicylic acid (SA) has been increasingly recognized in improved plant abiotic stress-tolerance via SA-mediated control of major plant-metabolic processes. However, the basic biochemical/physiological and molecular mechanisms that potentially underpin SA-induced plant-tolerance to major abiotic stresses remain least discussed. Based on recent reports, this paper: (a) overviews historical background and biosynthesis of SA under both optimal and stressful environments in plants; (b) critically appraises the role of SA in plants exposed to major abiotic stresses; (c) cross-talks potential mechanisms those are expected to govern SA-induced plant abiotic stress-tolerance; and finally (d) briefly highlights major aspects so far unexplored in the current context.